Proyecto de factibilidad para la producción y comercialización de gomitas a base de vodka sabor a manzana, en la Ciudad de Loja - Guiracocha Jiménez, Fabián Alexander (2024)
The subject covered by this feasibility project is about the implementation of a company that produces and markets apple-flavored vodka-based gummies in the city of Loja, where an exploratory type of research is conducted, using qualitative and quantitative methods, techniques, and research instruments that allow the collection, analysis, and interpretation of data. Consequently, a market study was conducted to know the tastes and preferences of its population, where it was determined that 94% of effective demand is willing to buy the product and an unsatisfied demand of 298,993,794 grams of gummies per year. Given this, the technical study covering the engineering of the project was carried out, where the capacity used was calculated at 13,200,000 grams per year, which covers 4.39% of the current market. In the legal and administrative study, the company was established as a limited liability company, and its corporate name is “Productora Gummies”. The economic research determined an investment of US$34,396.32 in the first year. The indicators of the financial evaluation indicated that the project is viable, with a positive Net Present Value (NPV) of $46,927.00; the Internal Rate of Return (IRR) is 54.49%, higher than the ARR (9.76%); the Capital Recovery Period (CRP) is 1 year, 10 months and 11 days; the Benefit-Cost Ratio (BCR) is 0.33 cents of profit for each dollar invested. The sensitivity analysis has a value of 0.99, less than 1, implying that the project's profitability is not sensitive to changes. The project withstands changes of up to 10.30% in the decrease of revenues and 13.75% in the increase of costs.